Seasonal Diets of the Denali Caribou Herd, Alaska - Boertje, Rodney D. (ARCTIC, 1984)
Food habits of the Denali (formerly McKinley) herd of barren-ground caribou (Rangifer tarandus granti) were studied during 1978-80 in Denali National Park, Alaska, with emphasis on diets of adult females. Data from fecal analyses, field observations, and forage digestibilities were combined to estimate diets. Spring (late May to July) diets contained primarily Salix leaves (41%), lichens (25%), forbs (16%), and graminoids (12%). Summer (mid-July to mid-August) diets were similar, containing about 46% Salix leaves, 17% lichens, 10% forbs, 10% graminoids, and 12% mushrooms. In contrast, autumn (mid-September to mid-October) diets consisted primarily of lichens (43%) with less proportions of forbs (9%). graminoids (14%), mushrooms (10%), and mosses (5%). Winter (mid-November to early May) diets consisted largely of lichens (62%) and small proportions of Vaccinium vitis-idaea (6%), forbs (7%), graminoids (11%), and mosses (10%).Key words: caribou, Denali National Park, diets, fecal analysis, food habits, Rangifer Mots clés: caribou, parc national Denali, régimes, analyse fécale, habitudes d'alimentation, Rangifer